2019
DOI: 10.12688/f1000research.15270.2
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in managing fecal incontinence

Abstract: Fecal incontinence (FI) is the uncontrolled passage of feces or gas in an individual who previously had control. The prevalence of the problem varies but can be as high as 50% of institutionalized individuals. The severity varies among individuals, but the negative impact on self-esteem and quality of life can have devastating effects. The goals of treatment are to decrease the frequency and severity of episodes as well as to improve quality of life. At present, several therapies, ranging from medical manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…By creating passive resistance, the device contributes to controlling faecal continence ( 65 ). While initial feasibility studies showed promise, due to high rates of significant events, complications and explanation, both this and dynamic graciloplasty are no longer available ( 78 ).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…By creating passive resistance, the device contributes to controlling faecal continence ( 65 ). While initial feasibility studies showed promise, due to high rates of significant events, complications and explanation, both this and dynamic graciloplasty are no longer available ( 78 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Although voluntary control of this muscle is limited, an implanted pulse generator can transform its properties over time, leading to improved faecal control ( 79 ). For similar reasons as for magnetic sphincters this technique is no longer popular or available ( 78 ).…”
Section: Treatmentmentioning
confidence: 99%
“…A life-altering condition that presents with an inability to maintain voluntary control of the passage of gas, liquid, or solid stool through the anus in patients who previously had control is defined as fecal incontinence [6,9]. Thus, most patients experience social isolation and decreased quality of life [1,2].…”
Section: Definition and Causes Of Fecal Incontinencementioning
confidence: 99%
“…When examining the patient, check for soiling, erythema of perineal skin, signs indicating previous trauma, and perform a squeeze test on DRE while assessing the symmetry of closure. Also, look for the rectum/anal canal descent by asking the patient to bear down (Valsalva maneuver) and look for the anal wink or anal cutaneous reflex to assess for pudendal injury [2,3,6,9].…”
Section: Physical Examinationmentioning
confidence: 99%
“…62 Casos que não respondem à abordagem inicial podem ser considerados para tratamento paliativo de suporte, que, hoje, inclui dispositivos de barreira mecânica não invasivos, como plugs anais e o plug vaginal. Esses dispositivos podem melhorar a qualidade de vida quando acessíveis e tolerados pelos pacientes, [63][64][65] no entanto, grande parte desses casos (especialmente quando há lesão da musculatura esfincteriana) terá indicação de cirurgia que varia desde procedimentos menos invasivos, como a esfincteroplastia e neuromodulação sacral (NMS), a procedimentos extensos e mutilantes, como técnicas de substituição de esfíncter e CD. [66][67][68] Esfincteroplastia, com ou sem sobreposição dos feixes esfincterianos, vem sendo realizada desde 1971, quando preconizada por Parks para reparo tardio de lesões esfincterianas pós-cirúrgica ou pós-parto.…”
Section: Introductionunclassified